Example
Solve:
−t2+t=0
Answer:
Each term has a common factor of t, so we can factor and use the zero product principle. Rewrite each term as the product of the GCF and the remaining terms.
−t2=t(−t)t=t(1)
Rewrite the polynomial equation using the factored terms in place of the original terms.
−t2+t=0t(−t)+t(1)t(−t+1)=0
Now we have a product on one side and zero on the other, so we can set each factor equal to zero using the zero product principle.
t=0 OR −t+1=0−1−1−t=−1−1−t=−1−1t=1
Answer
t=0 OR t=1
In the following video we show two more examples of using both factoring and the principle of zero products to solve a polynomial equation.
https://youtu.be/gIwMkTAclw8
In the next video we show that you can factor a trinomial using methods previously learned to solve a quadratic equation.
https://youtu.be/bi7i_RuIGl0
You and I both know that it is rare to be given an equation to solve that has zero on one side, so let's try another one.
Example
Solve:
s2−4s=5
Answer:
First, move all the terms to one side. The goal is to try and see if we can use the zero product principle, since that is the only tool we know for solving polynomial equations.
s2−4s=5s2−4s−5=0
We now have all the terms on the left side, and zero on the other side. The polynomials2−4s−5 factors nicely, which makes this equation a good candidate for the zero product principle. (imagine that)
s2−4s−5=0(s+1)(s−5)=0
We separate our factors into two linear equations using the principle of zero products.
(s−5)=0s−5=0s=5
OR
(s+1)=0s+1=0s=−1
Answer
s=−1 OR s=5
We will work through one more example that is similar to the one above, except this example has fractions, yay!
Example
Solve
y2−5=−27y+25
Answer: We can solve this in one of two ways. One way is to eliminate the fractions like you may have done when solving linear equations, and the second is to find a common denominator and factor fractions. Eliminating fractions is easier, so we will show that way.
Start by multiplying the whole equation by 2 to eliminate fractions:
2(y2−5=−27y+25)2(y2)+2(−5)=2(−27)+2(−25)2y2−10=−7y+5
Now we can move all the terms to one side and see if this will factor so we can use the principle of zero products.
2y2−10=−7y−52y2−10+7y−5=02y2−15+7y=02y2+7y−15=0
We can now check whether this polynomial will factor, using a table we can list factors until we find two numbers with a product of 2⋅−15=−30 and a sum of 7.
Factors of 2⋅−15=−30 |
Sum of Factors |
1,−30 |
−29 |
−1,30 |
29 |
2,−15 |
−13 |
−2,15 |
13 |
3,−10 |
−7 |
−3,10 |
7 |
We have found the factors that will produce the middle term we want,
−3,10. We need to place the factors in a way that will lead to a term of
10y:
(2y−3)(y+5)=0
Now we can set each factor equal to zero and solve:
(2y−3)=0 OR (y+5)=02y=3 OR y=−5y=23 OR y=−5
You can always check your work to make sure your solutions are correct:
Check
y=23
(23)2−5=−27(23)+2549−5=−421+25 common denominator = 449−420=−421+410−411=−411
y=23[/latex]isindeedasolution,nowcheck [latex]y=−5
(−5)2−5=−27(−5)+2525−5=235+2520=24020=20
y=−5 is also a solution, so we must have done something right!
Answer
y=23 OR y=−5
In our last video, we show how to solve another quadratic equation that contains fractions.
https://youtu.be/kDj_qdKW-ls